Sporties staying fit - Chan, Margaret Kit Yok (UiTM Sarawak, 2016)
Three lecturers who are members of the Sarawak Institute of Agriculture Scientists (SIAS) formed part of the Badminton team made up of Institute of Chemist Malaysia and Sarawak Veterinary Association in the Inter-professional Games 2015. They were Associate Prof. Dr. Margaret Chan Kit Yok who is a board member and two other badminton enthusiasts, Prof. Madya Dr. Voon Boo Hoo and Jong Li Ling. The theme for the game carnival was " Friendship through games". Though it was supposed to be friendly matches, the team put in a strong effort to win against the planners but could not fend off the strong accountants and the engineers.